When crop transgenes wander in California, should we worry? - N Ellstrand (California Agriculture, 2006)
The movement of transgenes into populations for which they are not intended remains a primary concern for genetically engineered crops. Such gene flow in itself is not a risk. However, we know that the transfer of genes from traditionally improved crops into wild populations has already resulted, on occasion, in the evolution of weeds more difficult to control, as well as an increased extinction risk for rare species. Just like traditional crops, genetically engineered crops could occasionally create the same problems. Currently in California, the movement of transgenes from most commercialized transgenic crops into wild plant populations is unlikely — the exception being canola. However, other transgenic plants have been field-tested in California, and if these become commercialized, in certain cases, transgenes are likely to move into the wild or into other crops of the same species. Such gene flow could result in various problems. The best containment for transgenes may involve risk assessment decisions by scientists embarking on projects to determine whether the proposed combination of organism and trait will pose any problems and if so, to determine how to create a safe product.